2021
DOI: 10.3390/su13031077
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainability of Industrial Heritage Tourism Far from the Axes of Economic Development in Europe: Two Case Studies

Abstract: The transformation of mining and industrial spaces into tourist spaces is part of the debate surrounding the profound changes in the contemporary economies of developed European countries. The loss of competitive power of their traditional companies, the obsolescence of many manufacturing facilities, and the take-off of other industrial economies in remote parts of the world have led to the closure of thousands of mines and factories, with the approval of environmental groups. In some privileged places, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 25 publications
0
48
0
1
Order By: Relevance
“…Overall, the utilization of industry-related cultural heritage tourism in this case study for more sustainable regional development shows rather sobering results, raising immediate questions about other similar regions. With some research on peripheral regions pointing to similar results [43,84,85], it can be concluded that industrial heritage tourism is not the solution for many problems facing (old) industrial regions. On the contrary, it is a rather difficult starting point.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Overall, the utilization of industry-related cultural heritage tourism in this case study for more sustainable regional development shows rather sobering results, raising immediate questions about other similar regions. With some research on peripheral regions pointing to similar results [43,84,85], it can be concluded that industrial heritage tourism is not the solution for many problems facing (old) industrial regions. On the contrary, it is a rather difficult starting point.…”
Section: Discussionmentioning
confidence: 88%
“…In the case of industrial heritage tourism and (to a lesser degree) industrial tourism, these impacts and results have not been clearly explored. Thus, a better assessment of the potentials and limits of industrial heritage tourism, especially in more peripheral regions, is needed (see [43] for an example). This is even more important in the case of cultural heritage items based on an industrial past and present, which are widely used with the overall aim of not only economic gain (i.e., tourism) but also often for other expected (social) benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kyrylov et al [19] analysed current trends and identified prospects for international tourism development in the context of increasing globalisation risks in the world. Using the German experience, the author of [24] demonstrated the positive effect of implementing project Industrial Heritage Trail on the economic development of the post-industrial region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the Spanish National Industrial Heritage Program, the definition of industrial heritage is the collection and management of movable and immovable assets produced through mining, transformation, transportation, distribution and other activities, as well as social systems related to working-class culture, and management. This is the industrial revolution-the result of the established economic system [5].…”
Section: Introduction 1protection and Reuse Of Industrial Heritagementioning
confidence: 99%